NILAI DIAGNOSTIK IgA ANTIVCA ANTIBODI EPSTEIN-BARR DI KARSINOMA NASOFARING - Betty Agustina Tambunan; Aryati Aryati; Windu Nafika (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2015)
Early diagnosis of nasopharyngeal carcinoma (NPC) is difficult, so most patients arrived already in an advanced stage. The biopsyas the gold standard for the diagnosis of NPC at an early stage also have limitations. Epstein-Barr virus as the cause of NPC is pavingthe way for early diagnosis was through serological method. The purpose of this study is to know the diagnostic value of IgA antiviralcapsid antigen (VCA) Epstein-Barr antibody for NPC by analyzing it. The samples were NPC patients and others whome have head-neckmalignancies arrived in the Oncology Outpatient Clinic, Dr. Soetomo Hospital. Their sera were examined for IgA antiVCA Epstein-Barrantibody using ELISA method and then analyzed for its diagnostic value using the 2x2 table with a 95% confidence interval. IgA antiVCAcutoff was determined by ROC. The results show that the diagnostic value of IgA antiVCA Epstein-Barr antibody have the sensitivityand specificity around 93.3% and 93.8%, respectively. Positive predict value was 96.6%% and the negative one was 88.2%, while thediagnostic efficiency was 93.5%. The positive likelihood ratio was 14.9 times and the negative was only 0.07. The cut off value of IgAantiVCA according ROC was 13.45 U/mL with AUC 97.9%. Based on this study, can be concluded that IgA antiVCA Epstein-Barr antibodyshowed an excellent validity in supporting the diagnosis of NPC. However, the researchers needed further research to know the obtainableearly stage of NPC.